1986
DOI: 10.1002/nur.4770090210
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among intensive care nurses

Abstract: The purpose of this study was to examine the relationship between intensive-care nurse burnout and demographic variables. The Maslach Burnout Inventory measured six components of burnout; emotional exhaustion frequency and intensity, depersonalization frequency and intensity, and personal accomplishment frequency and intensity. The sample (N = 89) was drawn from an army medical center. The variables, nursing, age, sex, military status, level of education, and length of time in nursing correlated with more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
4

Year Published

1987
1987
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 19 publications
4
33
0
4
Order By: Relevance
“…This general pattern of a significant negative correlation between age and scores on the depersonalization subscale, and often on the emotional exhaustion subscale, but not on the personal accomplishment subscale is consistent with findings among other professional groups (Bartz & Maloney, 1986;Jackson, Barnett, Stajich, & Murphy, 1993;Lee & Ashforth, 1991;Price & Spence, 1994). There are two theories that are most often suggested to account for these correlations.…”
Section: Introductionsupporting
confidence: 80%
“…This general pattern of a significant negative correlation between age and scores on the depersonalization subscale, and often on the emotional exhaustion subscale, but not on the personal accomplishment subscale is consistent with findings among other professional groups (Bartz & Maloney, 1986;Jackson, Barnett, Stajich, & Murphy, 1993;Lee & Ashforth, 1991;Price & Spence, 1994). There are two theories that are most often suggested to account for these correlations.…”
Section: Introductionsupporting
confidence: 80%
“…On a personal level, they might adopt successful strategies from other medical professions, as described in the literature, such as dental educators [30] and the army's intensive-care nurses. [31] Instead of maladaptive strategies (using alcohol, smoking, or taking drugs) that will not resolve the problem, some proposed solutions that may be applicable for EPs include exercise, communication with other colleagues, regular rest and relaxation, and experiencing new hobbies or interests. [32] …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in the human service fields have identified a negative relationship between age and burnout (Bartz & Maloney, 1986;Jenkins & Ostchega, 1986;Rich & Rich, 1987;Rosenthal, Schmid, & Black, 1989). More specifically in education, many authorities feel the greatest risk of burnout occurs during the first 3 years of teaching (Cherniss, 1980;Hamberger, & Stone, 1983).…”
mentioning
confidence: 96%